A rare complication related to H1N1 infection: Dilated cardiomyopathy - Türe, Mehmet; Gözü Pirinççioğlu, Ayfer; Akın, Alper; Balık, Hasan; İlter, Seçkin and Yanmaz, Sercan Yücel (The European Research Journal, 2018)
The symptoms and findings of influenza A (H1N1) resemble the symptoms and findings of seasonal influenza and it generally emerges as an upper respiratory tract disease. Although the majority of patients with the influenza A virus recover spontaneously without complications, there have been occasional reports of myopericarditis. However the most frequent complications have been reported as viral pneumonia and more rarely dilated cardiomyopathy. In this paper, we report a 4-month-old infant, who admitted with shortness of breath, cough, tachycardia and respiratory problems and was diagnosed as having developed dilated cardiomyopathy associated with H1N1.